CXCR2 inhibition suppresses acute and chronic pancreatic inflammation. Issue 1 (4th June 2015) - Steele, Colin W; Karim, Saadia A; Foth, Mona; Rishi, Loveena; Leach, Joshua DG; Porter, Ross J; Nixon, Colin; Jeffry Evans, TR; Carter, C Ross; Nibbs, Robert JB; Sansom, Owen J; Morton, Jennifer P
Abstract Pancreatitis is a significant clinical problem and the lack of effective therapeutic options means that treatment is often palliative rather than curative. A deeper understanding of the pathogenesis of both acute and chronic pancreatitis is necessary to develop new therapies. Pathological changes in pancreatitis are dependent on innate immune cell recruitment to the site of initial tissue damage, and on the coordination of downstream inflammatory pathways. The chemokine receptor CXCR2 drives neutrophil recruitment during inflammation, and to investigate its role in pancreatic inflammation, we induced acute and chronic pancreatitis in wild‐type and Cxcr2−/− mice. Strikingly, Cxcr2−/− mice were strongly protected from tissue damage in models of acute pancreatitis, and this could be recapitulated by neutrophil depletion or by the specific deletion of Cxcr2 from myeloid cells. The pancreata of Cxcr2−/− mice were also substantially protected from damage during chronic pancreatitis. Neutrophil depletion was less effective in this model, suggesting that CXCR2 on non‐neutrophils contributes to the development of chronic pancreatitis. Importantly, pharmacological inhibition of CXCR2 in wild‐type mice replicated the protection seen in Cxcr2−/− mice in acute and chronic models of pancreatitis. Moreover, acute pancreatic inflammation was reversible by inhibition of CXCR2. Thus, CXCR2 is critically involved in the development of acute and chronic pancreatitis in mice, and its inhibition or loss protects against pancreatic damage. CXCR2 may therefore be a viable therapeutic target in the treatment of pancreatitis. © 2015 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.